Analisis Peserta Didik dalam Menyelesaikan Soal Pisa Ditinjau Dari Self-Efficacy Peserta Didik - Rochimatul Laili; Nur Fauziyah (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
The ability to solve mathematical problems can be obtained by the students if they have one of the affective abilities, namely self-efficacy. This study aims to describe student’s ability to solve PISA questions in terms of student's self-efficacy. Type of this study is descriptive-quantitative. The study was conducted in class VIII-G of SMPN 2 Gresik as many as 32 students in 2018/2019 academic year. The method used in this study is the questionnaire method and test method. The questionnaire method was used to knowing the category of self-efficacy obtained by students. While the test method is used to describe the ability of students to solve PISA questions. Based on the results of the data analysis test, it can be concluded that in the class VIII-G of SMPN 2 Gresik there were 28% of subjects having very high self-efficacy, 31% with high category, 38% with medium category, and 3% with low category. The percentage of subjects in class VIII-G in solving PISA questions based on their level, there were 22,6% at level 1, 22,6% at level 2, 21,7% at level 3, 15,6% at level 4, 7,5% at level 5 and 10,1% at level 6.